Desenvolvimento de aços de baixa densidade FeMnAlC com adição de Ti e B: influência do processamento na microestrutura e nas propriedades - Vidilli, André Luiz (Universidade Federal de São Carlos, 2024)
The FeMnAlC steels are highlighted in the current scientific field thanks to the great demand from the automotive industry for advanced materials with high specific strength. Aluminum is one of the main elements responsible for reducing density. However, this element also reduces the modulus of elasticity, limiting their applications. In this context, incorporating ceramic particles with low density and high modulus of elasticity, is a promising strategy to reestablish the value of modulus of elasticity, further reducing density and improving the performance of these materials. The present study evaluated the effect of the addition of Ti and B on the microstructure and physical and mechanical properties of steels from the FeMnAlC system, produced by different processing routes, aiming to obtain a composite with a metallic matrix reinforced with TiB2 particles. The first stage involved thermodynamic calculations - CALPHAD method - and the production of the composites by the arc melting route to study the influence of the steel's alloying elements on the in-situ formation of the TiB2. It was concluded that carbon is a key element since its presence reduces the formation of TiB2. The effect of the matrix and the fraction of TiB2 particles - 5% and 10% by volume - was evaluated through spray forming route. After selecting the composite with the best combination of properties, the microstructural, physical, and mechanical implications associated with processing by laser powder bed fusion were studied. The high cooling rates promoted substantial microstructural refinement but suppressed the formation of the target TiB2. Instead, the complex (Fe,Mn)2B was formed. Based on the comparison between processing routes, the composite with a ferritic matrix reinforced with 5% vol. of TiB2, processed by spray forming, stood out with the best combination of properties.
Design of lightweight FeMnAlC steels with Ti and B addition: influence of processing on microstructure and properties
Keywords: Aços de baixa densidade; Lightweight steels; Diboreto de titânio; Titanium diboride; Compósitos; Composites; Fusão a arco; Arc-melting; Conformação por spray; Spray forming; Fusão seletiva a laser; Laser powder bed fusion; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA